Homocysteine—a retrospective and prospective appraisal - McCaddon, Andrew; Miller, Joshua W. (Frontiers in Nutrition, 2023)
The biologically important amino acid homocysteine links sulfur, methionine, and one-carbon metabolism. This review describes its initial discovery, the identification of the clinical condition of ‘homocystinuria’ and the recognition of its close relationship to folate and vitamin B12 metabolism. It discusses the history behind its current association with diverse diseases including neural tube defects, cardio- and cerebrovascular disease and, more recently, dementia and Alzheimer’s Disease. It also explores current controversies and considers potential future research directions. It is intended to give a general overview of homocysteine in relation to health and disease.